2022
DOI: 10.3892/ol.2022.13303
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors in sarcoma treatment (Review)

Abstract: Sarcomas are a group of rare mesenchymal malignant tumors that arise from transformed cells of the mesenchymal connective tissue, which are challenging to treat. The majority of sarcomas are soft tissue sarcomas (STSs; 75%) and this heterogeneous group of tumors is further comprised of gastrointestinal stromal tumors (~15%) and bone sarcomas (10%). Although surgery remains the current primary therapeutic approach for localized disease, recurrent, metastatic and refractory sarcomas require cytotoxic chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Recently, TRK inhibitors, larotrectinib, and entrectinib, have been approved by the Food and Drug Administration (FDA) to treat advanced or metastatic NTRK- rearranged cancers, including sarcoma 44. Other tyrosine kinase inhibitors are also used in treating mesenchymal tumors with kinase fusions in clinical trials 45…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TRK inhibitors, larotrectinib, and entrectinib, have been approved by the Food and Drug Administration (FDA) to treat advanced or metastatic NTRK- rearranged cancers, including sarcoma 44. Other tyrosine kinase inhibitors are also used in treating mesenchymal tumors with kinase fusions in clinical trials 45…”
Section: Discussionmentioning
confidence: 99%
“…22 Noteworthily, although the development of targeted drugs was scanty own to the heterogeneity of STS and the absence of driver mutation, some previous work had explored that the angiogenetic pathway might be one of the promising targets clinically. 23 Patients included in the present study were the metastatic STS who had received at least first-line systemic chemotherapy treatment, similar as the baseline characteristics of ALTER0203 clinical trial, which suggested that the combination administration of anlotinib plus PD-1 blockades was reasonable and ethical, given that anlotinib had the indication for patients with previously treated metastatic STS in China. To our knowledge, the ORR and DCR of anlotinib monotherapy for patients with previously treated metastatic STS was 13% and 74%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“… 22 Noteworthily, although the development of targeted drugs was scanty own to the heterogeneity of STS and the absence of driver mutation, some previous work had explored that the angiogenetic pathway might be one of the promising targets clinically. 23 …”
Section: Discussionmentioning
confidence: 99%
“…For unresectable and metastatic STS, chemotherapy including doxorubicin and cyclophosphamide has recommended for decades, although with limited efficacy (1). Some clinical trials of small sample size on advanced sarcoma have indicated that anlotinib (10,11) or immunotherapy (12,13) are potential treatment options in chemotherapy-resistant patients and the objective response rate (ORR) ranges from 13% to 40%. However, a standard treatment for USRCS is still unavailable.…”
Section: Discussionmentioning
confidence: 99%